2021
DOI: 10.3390/ijms22158217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Central Hypogonadism

Abstract: Reproductive function depends upon an operational hypothalamo–pituitary–gonadal (HPG) axis. Due to its role in determining survival versus reproductive strategies, the HPG axis is vulnerable to a diverse plethora of signals that ultimately manifest with Central Hypogonadism (CH) in all its many guises. Acquired CH can result from any pituitary or hypothalamic lesion, including its treatment (such as surgical resection and/or radiotherapy). The HPG axis is particularly sensitive to the suppressive effects of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 121 publications
(192 reference statements)
0
9
0
6
Order By: Relevance
“…Regarding psychosis spectrum disorders, in the presence of obesity the male overrepresentation typically observed in epidemiological studies only occurred in the first half of life with women matching male diagnoses rates around the age of 40 and surpassing them beyond this age. This may be owed to a reduced protective effect of female sex hormones against psychosis onset in women with obesity, potentially mediated by altered hypothalamus-pituitary-adreno signaling that accelerates the rise in psychosis spectrum disorders commonly observed in perimenopausal states [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding psychosis spectrum disorders, in the presence of obesity the male overrepresentation typically observed in epidemiological studies only occurred in the first half of life with women matching male diagnoses rates around the age of 40 and surpassing them beyond this age. This may be owed to a reduced protective effect of female sex hormones against psychosis onset in women with obesity, potentially mediated by altered hypothalamus-pituitary-adreno signaling that accelerates the rise in psychosis spectrum disorders commonly observed in perimenopausal states [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…INSR and other components of insulin signaling are present in all of these populations of hypothalamic neurons, although they are not found in GnRH-expressing neurons. It is important that the adipokine leptin uses the same mechanisms to stimulate GnRH production, being an insulin synergist in the activation of the hypothalamic links of the gonadal axis [ 354 , 355 ].…”
Section: Intranasal Insulin and The Gonadal And Thyroid Systemsmentioning
confidence: 99%
“…However, in obese people, the hypothalamus becomes resistant to leptin. This leads to reduced expression of the gene for kisspeptin, and consequently, reduced GnRH secretion [ 184 ]. It was found that leptin might also modulate the expression and release of gonadotropins [ 183 ].…”
Section: Schizophrenia and Obesitymentioning
confidence: 99%